Treatment of rheumatoid arthritis-associated interstitial lung disease: a perspective review. (December 2015) - Iqbal, Kundan; Kelly, Clive
Rheumatoid arthritis (RA) is a systemic autoimmune disease affecting 0.5–1% of the worldwide population. Whilst predominantly causing chronic pain and inflammation in synovial joints, it is also associated with significant extra-articular manifestations in a large proportion of patients. Among the various pulmonary manifestations, interstitial lung disease (ILD), a progressive fibrotic disease of the lung parenchyma, is the commonest and most important, contributing significantly to increased morbidity and mortality. The most frequent patterns of RA-associated ILD (RA-ILD) are usual interstitial pneumonia and nonspecific interstitial pneumonia. New insights during the past several years have highlighted the epidemiological impact of RA-ILD and have begun to identify factors contributing to its pathogenesis. Risk factors include smoking, male sex, human leukocyte antigen haplotype, rheumatoid factor and anticyclic citrullinated protein antibodies (ACPAs). Combined with clinical information, chest examination and pulmonary function testing, high-resolution computed tomography of the chest forms the basis of investigation and allows assessment of subtype and disease extent. The management of RA-ILD is a challenge. Several therapeutic agents have been suggested in the literature but as yet no large randomized controlled trials have been undertaken to guide clinical management. Therapy is further complicated by commonly prescribed drugs of proven articular benefit such as methotrexate, leflunomide (LEF) and anti-tumour necrosis factor α agents having been implicated in both ex novo occurrence and acceleration of existing ILD. Agents that offer promise include immunomodulators such as mycophenolate and rituximab as well as newly studied antifibrotic agents. In this review, we discuss the current literature to evaluate recommendations for the management of RA-ILD and discuss key gaps in our knowledge of this important disease.